(untitled) (Research, Society and Development, 2022)
Traffic light intersections tend to be the most problematic places in the road systems, as they present high levels of congestion, accidents, air pollution and high economic losses. With this, the methods and models that provide knowledge of the efficiency parameters of the operation become more and more protagonists in the management of urban traffic. However, the availability of different methods and models can lead to divergence between the parameters within the same intersection. Thus, this study aims to analyze how the application of statistical tests allows the identification of relevant instruments for traffic management. The methodology consists of using two VISSIM and Simtraffic simulators, and the Webster method to obtain the parameters of operation efficiency, average delay and the queue length of the tail of a traffic light intersection with three accesses. For the analysis of the parameters, taking into account different methods and models, in three traffic light cycles, the statistical tests of ANOVA and Mann-Whitney were applied. The results show the importance of applying these tests to improve urban traffic management, since these tests determine whether the operational efficiency parameters differ according to the scenario, methods and software applied.